Aligning National Legal Development with Local Wisdom: A Study in the Special Region of Yogyakarta - Supono, Supono; Prasetyoningsih, Nanik; Adilah, Indira Naquita (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to detail and explain the alignment of national legal development with local wisdom, focusing on case studies in the Special Region of Yogyakarta. Through this review, this research seeks to provide a deeper understanding of how national law can be integrated with the rich local values in DIY. The method used in this research is a qualitative approach that involves several data collection techniques, including literature study, observation, and stakeholder interviews. The research results show the relevance and positive impact of aligning national legal development with local wisdom in the Special Region of Yogyakarta (DIY). By analyzing the role of local wisdom in developing national law, this research highlights the integration of traditional values with legal principles that apply nationally. The contribution of local wisdom, such as the spirit of justice, deliberation for consensus, and respect for human rights, has been proven to encourage the creation of an inclusive and effective legal system. In implementing legal development, the principle of legal pluralism is the primary basis, enabling the implementation of various dispute resolution mechanisms and natural resource management that respect cultural diversity and local values. This research also highlights concrete efforts in integrating local wisdom in national legal development, such as developing customary law that is in harmony with national law, integrating local wisdom in legal education, and empowering communities in applying traditional values in dispute resolution.